Talking about maps (Historia, 2021)
The basis of philosophy, the guidance to common-sense and sound living, is the whole history of mankind. And in the course of its study we learn to understand what natural forces have influenced the develop-ment of man; what individual groups of men have to contend with climatic- ally, and thus how a way of living, and an attitude towards living, develops. Yet becau.~e great civilisations have developed over long periods of human existance in widely separated and differential parts of the world, and because great minds and deathless prophets have been no exclusive phenomenon, history and geography as a study have become inseparable. ,50 it is that in "Talking "4bout Maps" the author, whose own interest for half a lifetime has been centred in this combined study, presents a brief outline of the partnership of Geography and History; and of the pictorial record which, describes the geographical discoveries and settle-ments of men.
Keywords: Geographical discoveries; Cartography; Settlements of men; Maps